A escola pelos olhos dos (as) estudantes: escuta, resistência e desejo de pertencimento. - Oliveira, Nayraline Barbosa de (2025)
This dissertation investigates adolescents' and young people's perceptions of their place in school, focusing on the promises and contradictions of institutional practices of listening, participation, and autonomy. The research combines theoretical foundations of Critical Theories of Education (Pierre Bourdieu, Jean-Claude Passeron, and Michel Foucault) with emancipatory and democratic approaches (Paulo Freire, Florestan Fernandes, Anísio Teixeira, and Darcy Ribeiro), seeking to understand how schoolchildren construct senses of belonging and agency in spaces marked by disciplinary norms, inequalities, and symbolic disputes. The methodology combines qualitative and quantitative analyses, based on questionnaires and focus groups administered in three schools in Fortaleza, Ceará (two public and one private), encompassing distinct sociocultural realities. The analysis of the empirical material allowed us to identify thematic axes on youth empowerment, mental health, relationships with teachers, and school structure, revealing tensions between the discourse of citizenship development and the reality marked by silencing and symbolic exclusion. The results indicate that, although student participation initiatives exist, they are often limited. Listening to students highlights demands for spaces for dialogue, recognition, and identity expression. By proposing a sociological reading of the school based on the voices of students, the work contributes to strengthening more inclusive, critical, and emancipatory educational practices.